Lateralizing value of semiology in medial temporal lobe epilepsy. (9th April 2015) - Dupont, S.; Samson, Y.; Nguyen‐Michel, V.‐H.; Zavanone, C.; Navarro, V.; Baulac, M.; Adam, C.
<x xml:space="preserve">Abstract</x> Objectives Analysing the clinical characteristics of seizures constitutes a fundamental aspect of the presurgical evaluation of patients with medial temporal lobe epilepsy and unilateral hippocampal sclerosis (MTLE‐HS), the most frequent form of focal epilepsy accessible to surgery. We sought to retrospectively determine whether objective manifestations could have a reliable lateralizing value in a large population of MTLE‐HS patients and if their presence could help to identify those patients who would be seizure free after surgery. Material and methods We analysed the frequency and predictive lateralizing value of objective ictal and postictal signs in 391 patients with MTLE‐HS (183 left/208 right). Data were derived from chart review and not from blinded videoEEG analysis. Correlation between the presence of reliable lateralizing signs and postoperative outcome was performed in a subgroup of 302 patients who underwent surgery. Results Contralateral dystonic posturing was the most frequent and reliable lateralizing sign that correctly lateralized the focus in 96% of patients. Unilateral head/eye deviation was noted in 42% of the patients and predicted unilateral focus in 67%. Ipsilateral postictal nose wiping, contralateral clonus and hypokinesia correctly lateralized the focus in 75%, 81%, respectively, and 100 of patients but were less frequently depicted. Postictal aphasia was a strong lateralizing sign for left MLE‐HS. The presence of reliable lateralizing signs was not a predictor of seizure freedom. Conclusion Seizure semiology is a simple tool that may permit reliable lateralization of the seizure focus in MTLE‐HS. The presence of reliable lateralizing signs is not associated with a better postoperative outcome.